A Comparative Study of Water Quality Assessment of Kanke Dam, Hatia (Dhurwa) Dam and Getalsud (Rukka) Dam in Ranchi, Jharkhand, India (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Jharkhand (The Land of Forest) is the 28th state of the Indian Union was brought into existence by the Bihar reorganization Act on November 15th 2000. It is a state in eastern India and the states shares its border with the State of Bihar to the North, Uttar Pradesh to the northwest, Chhattisgarh to the West and Odisha to the South and West Bengal to the East. Jharkhand has an area of 79,714 km2 (30,778 sq. m). Jharkhand is the 15th largest state by area and is the 14th largest by population. The state is known for its beautiful Waterfalls and Hills. Jharkhand is famous for its rich minerals resources like Uranium, Mica, Bauxite, Granite, Gold, Silver, Graphite, Magnetite, Dolomite, Fireclay, Quartz, Field spar, Coal (32% of India), Iron, Copper (25% of India) etc. The forest and woodlands occupy more than 29% of the state which is amongst the highest in India. The total population of the state is 32, 988,134 as per the data of 2011 census, in which male population is about 16,930,315 and the female population is about 16,057,819. The state capital of Jharkhand is Ranchi. It is popularly known as “The City of Water Falls”. Ranchi is located in the southern part of the Chota Nagpur Plateau in the Indian states of Jharkhand. It is situated at a latitude of 23.35° N and a longitude of 85.33° E. it is at an average elevation of 651 meters (2,140 feet) above the sea level. The Ranchi city is known for its natural beauty. The climate of the city is moderate, with three well defined seasons: the cold weather season from November to February and it is the most pleasant part of the year. The high temperature in Ranchi is in December usually rise from about 50° F (10° C) into the low 70° F (low20° C) daily. The hot weather season lasts from March to mid-June, May being the hottest month and is characterized by daily high temperature in the upper 90° F (37° C) and low temperature in the mid 70° F (20° C).